Makna Makna dan Fungsi Surat Yasin dalam Tradisi Tahlilan Di Desa Pasir Kulon Kecamatan Karanglewas: Perspektif Living Qur’an - Arafah Qurota A’yun; Khusnul Khotimah; Mustain (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Yasin letter is one of the letters in the Qur'an that has a special position among Muslims. This letter is often read in various religious activities, such as tahlilan, grave pilgrimage, and joint prayer. This study examines the meaning and function of the Yasin letter in the tahlilan tradition using the perspective of the living Qur'an. Yasin letter is often read in tahlilan rituals as a form of prayer for the deceased and spiritual reflection for the congregation. This type of research is field research. Data analysis using descriptive qualitative data collection techniques with observation, interviews and documentation. Data analysis techniques through three stages, namely data presentation, data reduction and data retrieval. The results of this study, the meaning of the Yasin letter is very important in uniting and strengthening bonds among the residents of Pasir Kulon Village, including the Yasin letter teaches about monotheism, the power of Allah, belief in the day of resurrection as a group communication media, so that its function as a medium for communicating religious messages containing moral messages, spiritual, and Islamic values that are conveyed to the community verbally.